Analisis Alternatif Model Pembiayaan Pengelolaan Sampah untuk Pengembangan Pembangkit Listrik Tenaga Sampah - Dayang P Amaliah; M. F. Bin Masruhen; M. Y. Ibrahim; F. R. Abdullah (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2022)
This research aims to design alternative financing models using Islamic commercial and social financial instruments. To achieve this, the analytic network process (ANP) became a method used to determine the right alternative financing model by using Islamic commercial and social financial instruments for PLTSa. The results showed that the right financing model for PLTSa is a combined model, consisting of several sources of funding, namely, Government Financing, Private Financing and Waqf Institution Financing. The right government financing is stated budget, sukuk and Islamic investment. Private financing consists of Syndication of Islamic Banks and corporations, in the financing of waqf institutions namely productive waqf & Infak and waqf, productive waqf & infak.